2020
DOI: 10.1038/s41467-020-14610-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influence is linked to cortical morphology in category-selective areas of visual cortex

Abstract: Human visual cortex contains discrete areas that respond selectively to specific object categories such as faces, bodies, and places. A long-standing question is whether these areas are shaped by genetic or environmental factors. To address this question, here we analyzed functional MRI data from an unprecedented number (n = 424) of monozygotic (MZ) and dizygotic (DZ) twins. Category-selective maps were more identical in MZ than DZ twins. Within each category-selective area, distinct subregions showed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
3
11
0
Order By: Relevance
“…A region of interest (ROI) approach was used as this is known to improve signal to noise ratio in fMRI. We hypothesized a genetic influence on brain function in areas of the ventral visual stream consistent with previous reports (Abbasi et al, 2020 ; Polk et al, 2007a ). We also expected a genetic influence on brain responses related to viewing distance and interpersonal distance, although we did not have specific hypotheses in which brain areas effects would be observed.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…A region of interest (ROI) approach was used as this is known to improve signal to noise ratio in fMRI. We hypothesized a genetic influence on brain function in areas of the ventral visual stream consistent with previous reports (Abbasi et al, 2020 ; Polk et al, 2007a ). We also expected a genetic influence on brain responses related to viewing distance and interpersonal distance, although we did not have specific hypotheses in which brain areas effects would be observed.…”
Section: Introductionsupporting
confidence: 81%
“…The source of individual variation in activation to social stimuli in the fusiform face area has been suggested to be partially genetic, as a study found greater correlation between identical than fraternal twin pairs in this area (Polk et al, 2007b ). Using a larger sample of twins from the Human Connectome Project, the finding of a genetic influence in face‐related activation of the fusiform face area has been replicated (Abbasi et al, 2020 ). Genetic influences on activation serving face perception were also observed in the lateral OFA (Abbasi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several hypotheses have been put forward to explain the consistent localization of category-selective regions across individuals, including: i) genetics, which may innately determine the location of these regions (Abbasi et al, 2020;McKone et al, 2012;Polk et al, 2007), ii) foveal and peripheral eccentricity biases coupled with consistent viewing demands of certain stimuli (e.g., foveation on words during reading) (Malach 2012;Dehaene 2015;Behrmann and Plautt 2015;Hasson et al, 2002), (iii) the underlying cortical microarchitecture, which is supported by the observation that different category-selective regions are located within different cytoarchitectonic regions of VTC Weiner et al, 2017) and iv) white matter connections, as category-selective regions are part of more extended brain networks and hence need to communicate with other regions across the brain (Haxby et al, 2000;Osher et al, 2016;Papagno et al, 2011;Saygin et al, 2016Saygin et al, , 2012. Note that these hypotheses are not mutually exclusive as all of these factors together may constrain the location of functional regions (e.g., see Behrmann and Plaut, 2015a for a unifying framework).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is suitable for post-surgery follow-up examinations because it provides useful information for various diagnoses without using a contrast agent. In recent years, functional MRI (fMRI) for studying brain functions has been developed, and its application in various fields, such as neuroscience, psychiatry, and psychology, has yielded a considerable amount of research data (Abbasi et al 2020;Achterberg et al 2020;Saker et al 2020). An MRI system uses magnetic fields and radiofrequency (RF) pulses to acquire signals from nuclear spins of protons in a subject and processes the signals to create images.…”
Section: Introductionmentioning
confidence: 99%